Primary Ovarian Large B-Cell Lymphoma - Mine Islimye Taskın; Levent Gokgozoglu; Bedrı Kandemır (Hindawi Limited, 2013)
The involvement of the ovary by malignant lymphoma is a well-known late manifestation of disseminated nodal disease. Primary ovarian lymphoma is rare. We herein describe a case of primary ovarian diffuse large B-cell lymphoma involving unilateral ovary in a 38-year-old woman which was detected incidentally. Preoperative ultrasonic imaging showed a 46*42 mm heterogeneous cystic mass. Laparotomy revealed that left adnexal mass and left salpingo-oophorectomy was performed. The current diagnosis was determined after immunostaining. The patient was treated with R-CHOP regimen after the operation. She remains cancer-free 24 months after chemotherapy.